Activated Protein C Resistance and the FV:R506Q Mutation in a Random Population Sample - Lowe, Gordon D. O.; Rumley, Ann; Woodward, Mark; Reid, Evan; Rumley, Joseph (Thrombosis and Haemostasis, 1999)
Activated protein C (APC) resistance, defined as a low APC ratio, is associated with the factor V mutation R506Q (factor V Leiden). APC ratio may also be influenced by other clinical and coagulation variables, which we studied in 460 men and 495 women aged 25-74 years, from a random population sample (Glasgow MONICA Survey). APC ratio correlated positively with APTT; and inversely with factor VIIIc, factor IXc, antithrombin activity, prothrombin F1+2 fragment, and thrombinantithrombin complexes; but not with other coagulation variables. APC ratio decreased with age, but APTT did not. APC ratio and APTT were significantly lower in women versus men, and were significantly lower in users of oral contraceptives or hormone replacement therapy. The FV:R506Q mutation (prevalence 2.5%) was associated with lower APC ratio and protein C and S activities and with higher factor VIIIc levels; but not with increases in F1+2 fragment or thrombin-antithrombin complexes. APC ratio correlated inversely with total cholesterol and diastolic blood pressure; and in women with triglycerides, systolic blood pressure, and body mass index. Obesity was associated with a significantly lower APC ratio. In contrast, smoking markers correlated positively with APC ratio in men. These associations of APC ratio may be relevant to the increased risks of venous thrombosis with age, female sex, oestrogen use, obesity and high factor VIIIc levels. The association of APC resistance with elevated plasma levels of coagulation markers suggests that this phenotype represents an in vivo hypercoagulable state.Current address: Dr. E. Reid, Department of Medical Genetics, Addenbrooke’s Hospital, Cambridge, UK